2023
DOI: 10.1088/1361-6560/aca1f2
|View full text |Cite
|
Sign up to set email alerts
|

GPU-accelerated Monte Carlo simulation of electron and photon interactions for radiotherapy applications

Abstract: Objective. The Monte Carlo simulation software is a valuable tool in radiation therapy, in particular to achieve the needed accuracy in the dose evaluation for the treatment plans optimisation. The current challenge in this field is the time reduction to open the way to many clinical applications for which the computational time is an issue. In this manuscript we present an innovative GPU-accelerated Monte Carlo software for dose valuation in electron and photon based radiotherapy, developed as an update of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Nevertheless, electrons are more flexible and can easily reach high DPP values necessary to trigger the flash effect compared to protons. Franciosini et al have shown with Monte Carlo simulations that an energy of 100-250 MeV, multiple fields and a pencil beam scan are required to obtain satisfactory dosimetric conformations in cases of deep tumors by using fields of few mm (80). For this reason, new linear accelerators able to deliver UHDR with high-energy electrons (VHHE) must be developed in the future for these treatments.…”
Section: Flash Experimental Questionmentioning
confidence: 99%
“…Nevertheless, electrons are more flexible and can easily reach high DPP values necessary to trigger the flash effect compared to protons. Franciosini et al have shown with Monte Carlo simulations that an energy of 100-250 MeV, multiple fields and a pencil beam scan are required to obtain satisfactory dosimetric conformations in cases of deep tumors by using fields of few mm (80). For this reason, new linear accelerators able to deliver UHDR with high-energy electrons (VHHE) must be developed in the future for these treatments.…”
Section: Flash Experimental Questionmentioning
confidence: 99%
“…However, in clinical radiotherapy more accurate dose calculation methods, such as the Monte Carlo algorithm, and higher computational efficiency are expected. In recent years, there have been two primary strategies to improve the computational efficiency of the Monte Carlo algorithm: simplifying the calculation algorithm, or using graphic processing unit (GPU) acceleration technology (Fippel 1999, Franciosini et al 2023. A recently proposed dose calculation method combining deep learning and the Monte Carlo algorithm, considering the calculation accuracy and computational efficiency, holds the potential for generalisation to dose calculation algorithms used in clinical practice (Kontaxis et al et al 2020, Neph et al 2021, Xiao et al 2022, Zhang et al 2022.…”
Section: Introductionmentioning
confidence: 99%